Populism and Liberal Constitutionalism: A Proposal to Define the Impact of Populism on the Constitutional Framework - Szentgáli-Tóth, Boldizsár; Simonelli, Marco Antonio (Public Governance, Administration and Finances Law Review, 2023)
Our paper focuses on the impact of populism on the functioning of constitutional democracy in Europe. To analyse such a complex issue, a survey has been elaborated, which tries to outline how the current populist tendencies influence the institutional framework of constitutional democracy and to what extent such parties aim and are able to undermine the long-term prevalence of rule of law. To achieve this goal, the survey monitors, amongst others, the use of referenda in European countries; the presence of instruments of participatory and direct democracy; which are the political programme of populist parties, and in particular what are their ambitions concerning institutional reforms; whether the status, the independence, the competence and the composition of the constitutional court and the judiciary are contested. The survey also examines whether the protection standard of the most important fundamental rights are relativized, or are intended to be relativized by the populist parties of the different countries. We approached young constitutional scholars from certain member states, at the initial stage of their academic career, and asked them to fill the survey.